Cover Feature: Incorporation of Cu/Ni in Ordered Mesoporous Co‐Based Spinels to Facilitate Oxygen Evolution and Reduction Reactions in Alkaline Media and Aprotic Li−O2 Batteries (ChemSusChem 5/2022). Issue 5 (15th February 2022) - Priamushko, Tatiana; Budiyanto, Eko; Eshraghi, Nicolas; Weidenthaler, Claudia; Kahr, Jürgen; Jahn, Marcus; Tüysüz, Harun; Kleitz, Freddy
Abstract : The Cover Feature shows the structure of the mesoporous mixed metal oxide bifunctional electrocatalyst with a magnification of the crystalline spinel structure building the framework walls. More information can be found in the Research Article by T. Priamushko et al .